Synthesis of Iron Oxide (Fe2O3)-Xanthan Gum Nanoparticle Composites Its Potential as a Chemical Flooding Media in Enhanced Oil Recovery (EOR) - Yong Richard Sriwijaya; Paramita Jaya Ratri; Tirta Rona Mayangsari; Azis Adharis; Shabrina Sri Riswati (Syarif Hidayatullah State Islamic University, 2023)
Increasing oil consumption in Indonesia encourages an improvement of production using chemical flooding of Enhanced Oil Recovery (EOR) technology. Chemical flooding is an injection method of materials based on polymer and nanoparticles such as α-Fe2O3-xanthan gum nanocomposite into the reservoir. In this study, α-Fe2O3 nanoparticles were synthesised and then blended to xanthan gum by sonochemical method through an ex-situ process. The α-Fe2O3-xanthan gum nanocomposite X-ray diffraction (XRD) shows that there are no additional peaks. Only the α-Fe2O3 and the xanthan gum peaks are detected with the crystallite size of around 16-20 nm. The particle size of α-Fe2O3-xanthan gum (1:1) nanocomposite as measured by Particle Size Analyzer (PSA) was 228.43 nm with the type of polydisperse. The functional group of the nanocomposite is a combination of the α-Fe2O3 and xanthan gum functional groups which shows there are no other compounds detected in IR spectra. The EOR test showed that xanthan gum had a significant effect on increasing the viscosity of the α-Fe2O3-xanthan gum nanofluid to 1.964 cP at a 1:2 composition. Based on these results, α-Fe2O3-xanthan gum nanofluid is the potential material used in the chemical flooding process in the reservoir.